Fuzzy-based composite indicator development methodology for evaluating overall project performance - Yu, Jung-Ho; Jeon, Me-Yeon; Kim, Tae Wan (Journal of Civil Engineering and Management, 2015)
Construction companies develop and use composite indicators to evaluate their overall project performance. However, the conventional methodology of composite indicator development causes “the indiscrimination problem”, a low degree of performance discrimination due to low resolution of measurement, and “the redundancy problem”, an incorrect evaluation caused by interrelation among sub-indicators. To address these problems, we propose a novel methodology that uses fuzzy theories. The proposed methodology includes the utility function for normalizing, the fuzzy measure for weighting, and the fuzzy integral for aggregating. A retrospective case study on 52 real projects shows that our proposed methodology can help alleviate the indiscrimination and redundancy problems: the proposed methodology significantly improved the degree of performance discrimination (0.29 to 0.92) and changed ranks of under- or overestimated projects by taking the interactions of sub-indicators into account. Our methodology can contribute more accurate evaluation of overall project performance with higher degrees of performance discrimination.